A low-mass stellar companion to the young variable star RZ Psc. (20th May 2020) - Kennedy, Grant M; Ginski, Christian; Kenworthy, Matthew A; Benisty, Myriam; Henning, Thomas; van Holstein, Rob G; Kral, Quentin; Ménard, François; Milli, Julien; Quiroga-Nuñez, Luis Henry; Rab, Christian; Stolker, Tomas; et al.
ABSTRACT: RZ Psc is a young Sun-like star with a bright and warm infrared excess that is occasionally dimmed significantly by circumstellar dust structures. Optical depth arguments suggest that the dimming events do not probe a typical sightline through the circumstellar dust, and are instead caused by structures that appear above an optically thick mid-plane. This system may therefore be similar to systems where an outer disc is shadowed by material closer to the star. Here, we report the discovery that RZ Psc hosts a $0.12\, M_\odot$ companion at a projected separation of 23 au. We conclude that the disc must orbit the primary star. While we do not detect orbital motion, comparison of the angle of linear polarization of the primary with the companion's on-sky position angle provides circumstantial evidence that the companion and disc may not share the same orbital plane. Whether the companion severely disrupts the disc, truncates it, or has little effect at all will require further observations of both the companion and disc.